X-Ray Reverberation Mapping of Ark 564 Using Gaussian Process Regression - Lewin, Collin; Kara, Erin; Wilkins, Dan; Mastroserio, Guglielmo; Garcia, Javier A.; Zhang, Rachel C.; Alston, William N.; Connors, Riley; Dauser, Thomas; Fabian, Andrew; Ingram, Adam; Jiang, Jiachen; et al. (Astrophysical Journal, 2022)
Ark 564 is an extreme high-Eddington Narrow-line Seyfert 1 galaxy, known for being one of the brightest, most rapidly variable soft X-ray AGN, and for having one of the lowest temperature coronae. Here we present a 410-ks NuSTAR observation and two 115-ks XMM-Newton observations of this unique source, which reveal a very strong, relativistically broadened iron line. We compute the Fourier-resolved time lags by first using Gaussian processes to interpolate the NuSTAR gaps, implementing the first employment of multi-task learning for application in AGN timing. By fitting simultaneously the time lags and the flux spectra with the relativistic reverberation model RELTRANS, we constrain the mass at 2.3+2.6/-1.3x10(6)M?, although additional components are required to describe the prominent soft excess in this source. These results motivate future combinations of machine learning, Fourier-resolved timing, and the development of reverberation models.
CRIS-Team WoS Importer:2022-12-02